Loose parts : inspiring play in young children - Daly, Lisa.; Beloglovsky, Miriam (St. Paul, MN : Redleaf Press, 2015)
Loose parts are natural or synthetic found, bought, or upcycled materials that children can move, manipulate, control, and change within their play. Daly and Beloglovsky show you how using loose parts can help you capture children's curiosity, give free reign to their imagination, and motivate learning. By developing creative environments, children will be encouraged to explore critical thinking in a myriad of ways.
Introduction to loose parts -- Loose parts -- Senses -- Color -- Texture -- Sound -- Creativity -- Art -- Design -- Symbolic play -- Action -- Movement -- Transporting -- Connecting/disconnecting -- Inquiry -- Construction -- Investigation -- Correlation.
Includes bibliographical references.
Keywords: Play; Early childhood education -- Activity programs; Creative activities and seat work; Creative activities and seat work; Early childhood education -- Activity programs; Play